A 2D square ising-like susceptible-infected model for malware spread - Antonio, Kristine Eia S.; Banzon, Ronald S. (Quezon City National Institute of Physics, College of Science, University of the Philippines Diliman, 2011)
Malware does not spread in a computer network in exactly the same way as a medical epidemic in a biological community. When infected individuals are able to communicate infections without direct contact, which is the case for malware, the disease may no longer simply diffuse from the first infected individual. Also if the composition of the population changes as quickly as it does with computer networks, the dynamics of spread is further altered. In this work, a susceptible-infected (SI) epidemic on a 2D Ising lattice is used to model malware spread. The Ising spins are used to stimulate the online-offline state of computer units. A global infection probability is imposed on all susceptible units in the network regardless of their affinity to infective units.
Thesis (M.S.Physics)--University of the Philippines Diliman
Keywords: Ising model; Internet (Computer network) -- Security measures; Information superhighway -- Security measures; Data protection; Computer viruses; Malware (Computer software) -- Prevention